Do We Deliver What They Expect? Finding the Gap Between Users' Expected and Currently Received Library Services. - Ara, Mehvish; Soroya, Saira Hanif (Pakistan Library & Information Science Journal, 2018)
This research aims to assess tire service quality of public libraries of Lahore by evaluating the disparities between the users' expectation and currently received services. The survey method based on questionnaire was used. Four of the largest libraries in Lahore, in terms of services, collection and other facilities, were the population of the study. A sample of four hundred library users was selected with one hundred library users for each library based on convenience sampling. A modified LibQUAL+ tool was adopted to collect the data. The findings revealed that users have very high expectations regarding the accessibility of library's electronic resources from home or office, library website, printed material, availability of electronic information resource, modem equipment, tools that allow the users to find the material themselves, and provision of the information in an easy manner. The findings are helpful for public libraries' authorities to redcsign/upgradc the quality of library services, policies and procedures according to users' expectations and requirements.
Keywords: ACCESS control; INTERNET access for library users; LAHORE (Pakistan); LIBRARY public services; LIBRARY records; Libraries; Libraries and Archives; PUBLIC libraries; dept.ils

Information Science and Technology: An Introduction for Librarians (course Pack, 2nd Version) - Liu, Yan Quan (Create Space : Yan Quan Liu, 2018)
Keywords: Information science; Information technology; Information and Library Science; dept.ils; faculty_collection

Library Services for Mobile Users: A Library in the Palm of Your Hand - Liu, Yan Quan (CreateSpace, 2018)
This books is a print version of the online course ILS 440 Information Service Technology offered at Southern Connecticut State University. The course content includes the instructor's lecture notes, assignment instructions, assigned readings, discussions and coursework from students in the classes.
Keywords: Library applications; Public services (Libraries); Mobile communication systems; Technological innovations; dept.ils; faculty_collection

Transforming Library Service for the 21st Century User - Liu, Yan Quan (Createspace, 2018)
This book is a print version of the online course ILS508 User Services. The course content includes the instructor's lecture notes, assignment instructions, assigned readings, discussions an coursework from the students in the classes.
Keywords: Public services (Libraries); dept.ils; faculty_collection

Effect of different areal precipitation estimation methods on the accuracy of a reservoir runoff inflow forecast model - Zhong, Wei; Li, Ruirui; Liu, Yan Quan; Xu, Jin (Institute of Physics Publishing, 2018)
Areal precipitation estimation directly affects the accuracy of reservoir runoff inflow forecasts and flood dispatching decision-making. Because of the heterogeneous spatial and temporal precipitation distributions in large basins, inadequate precipitation stations normally have a negative impact on forecast accuracy. Using the Panjia-kou reservoir runoff inflow forecast as the research subject, this paper adopts the Thiessen polygon block, square grid computing, and DEM (digital elevation model) methods to estimate average regional areal precipitation. Based on the estimation, a model for the Panjia-kou reservoir runoff forecast is developed. The results indicate that different areal precipitation estimation methods have significantly different effects on the accuracy of the reservoir runoff inflow forecast. When the average regional precipitation estimation from the DEM method is used as an input to the model, the simulation results are accurate and are much better than those from the other two average regional precipitation estimation methods.
Keywords: Air pollution; Areal precipitation; Decision making; Different effects; Digital elevation model; Forecast accuracy; Forecasting; Grid computing; Precipitation distribution; Precipitation estimation; Research subjects; Reservoirs (water); Runoff; Runoff forecast; Surveying; dept.ils

The provision of mobile services in US urban libraries - Guo, Ya Jun; Liu, Yan Quan; Bielefield, Arlene (Information Technology and Libraries, 2018)
To determine the present situation regarding services provided to mobile users in US urban libraries, the authors surveyed 138 Urban Libraries Council members utilizing a combination of mobile visits, content analysis, and librarian interviews. The results show that nearly 95% of these libraries have at least one mobile website, mobile catalog, or mobile app. The libraries actively applied new approaches to meet each local community’s remote-access needs via new technologies, including app download links, mobile reference services, scan ISBN, location navigation, and mobile printing. Mobile services that libraries provide today are timely, convenient, and universally applicable.
Keywords: dept.ils; human; mobile application; peer-reviewed; printing; publication; review

Bullying in the library workplace - Kim, Hak Joon; Geary, Carol Anne; Bielefield, Arlene (Library Leadership & Management, 2018)
The primary purposes of the study were to investigate how often bullying occurs in libraries and whether bullying policies exist in libraries. The first survey questionnaire was sent to library personnel in the six New England states through statewide email distribution lists. Altogether 571 library staff members completed the survey. The second survey questionnaire was sent to large public and academic libraries in New England to see if they have anti-bullying policies in the workplace. The results of the study clearly showed there were significant reports of workplace bullying in all kinds of libraries. Nonetheless, not many libraries have policies that deal with this workplace challenge.
Keywords: bullying; bullying polices; dept.ils; library policies; workplace bullying

Rural and small public libraries: challenges and opportunities - Real, Brian (Advances in Librarianship, Volume 43, 2018)
Keywords: Rural libraries; Small libraries; dept.ils

The hidden history of the American Film Institute: the cold war, arts policy, and American film preservation - Real, Brian (The Moving Image: The Journal of the Association of Moving Image Archivists, 2018)
The American Film Institute (AFI) presently does relatively little in terms of film preservation, but its founding in 1967 led to the growth of many of the mechanisms that define the motion picture preservation community today. As this article reveals, the AFI's success in promoting ongoing federal government support for motion picture preservation cannot be separated from the political context of the Cold War. The AFI's first director, George Stevens Jr., had previously been the head of the Motion Picture Service of the United States Information Agency (USIA). This work with a public diplomacy agency was essential to his vision for the design and structure of the AFI. Likewise, the AFI was founded as an independent nonprofit, but with the promise of significant ongoing funding support from the National Endowment for the Arts (NEA). While this arrangement worked well at first, a change in presidential administrations and design flaws in the AFI's support mechanisms led to it being unable to meet the expectations of the very film preservation community it helped to foster.
Keywords: dept.ils; peer-reviewed